Resistance during the armed conflict in the Chocó, Colombia : a case study on the development of territorial and cultural resistance of the indigenous communities since the 1980s - Baumeister, Robert (2007)
This Master’s thesis aims to study the resistance process of the indigenous communities of the Colombian department of Chocó and the development of this process into potential grass-roots peace initiative via a particular form of identity reaffirmation through ancestral territories. Particularly, this studies focus on the conflict territorialization and the consequential inclusion of indigenous territories into the conflict logic, which has promoted the development of an indigenous resistance process derived from a defense of territories as basis for identity construction. The thesis illustrates the change of the logic of conflict and the resultant development of an indigenous organizational structure as part of a resistance process that hence can be termed territorial and cultural resistance. Hereby, the theoretical concept of ‘civil resistance’ is critically discussed and enhanced to conceptualize this particular notion of resistance by the indigenous peoples. This thesis follows a case study approach to qualitative analysis. Commencing with a regional analysis, the study’s findings are linked to a wider theoretical context and numerous practical issues. The empirical data of the thesis is drawn from multiple sources, using ‘triangulation’ by analyzing academic literature as well as brochures of selfpresentation, official denunciations, declarations and statements by the indigenous communities and their organizations. This data is complemented by several semistructured interviews with representatives of indigenous communities, their organizations, as well as government and NGO representatives. The study’s findings suggest that the indigenous communities have developed a resistance process through identity reaffirmation and the development of an organizational structure based on a ‘bottom-up-approach’. The organizational structure functions as an authority alternative and simultaneously integrates international advocacy networks to pressure the Colombian state. Hereby, the process has evolved into a potential grass-roots peace initiative to the Colombian armed conflict.